Horse Feeding and Management - Fradinho, Maria João (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Horses perform variety of roles in our society, serving people in several ways. Proper nutrition and feeding management are some of the main objectives to ensure the well-being and performance of horses. Thus, the link between equine health and good dietary treatment must be recognized to increase our understanding of the needs of the horse. It is important to ensure science-based knowledge is available to all stakeholders and people working in the horse industry. This book presents research papers published in the Special Issue of Animals entitled 'Horse Nutrition and Management'.